Studies in the Book of wisdom - Xeravits, Géza G.; Zsengellér, József. (Supplements to the Journal for the Study of Judaism, 2010)
The volume publishes papers delivered at the International Conference on the Deuterocanonical Books (Pápa, Hungary). This conference dealt with the Book of Wisdom. As such, this was one of the most extended discussions of the Book of Wisdom that has ever taken place at a scholarly meeting. The volume contains articles on the traditions and theology of the Book of Wisdom, and demonstrates its relationship with the contemporary literature of early Judaism and Middle Platonic thought.